2023
DOI: 10.1021/jacs.2c13207
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Fe/Ti Enabled Regioselective Arene Difunctionalization

Abstract: Regioselective difunctionalization of arenes remains a long-standing challenge in organic chemistry. We report a novel and general Fe/Ti synergistic methodology for regioselective synthesis of various polysubstituted arenes through either E/E′ or Nu/E ortho difunctionalizations of arenes. Preliminary results showed that an unprecedented 1,2-Fe/Ti heterobimetallic arylene intermediate bearing two distinct C–M bonds is essential to the regioselective difunctionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Although the exact structure of this species requires further exploration, our preliminary studies (HMRS and NMR) provide evidence for its formation. 15 Meanwhile, we confirmed that C−Ti and C−Fe bonds coexisted in this species by trapping of C−Ti and C−Fe bonds with different reactions. Using these reactions, we also compared the reactivity of C−Ti and C−Fe bonds in this bimetallic compound.…”
Section: Distinct Reactivity Of C−fe and C−ti Bondsmentioning
confidence: 52%
See 2 more Smart Citations
“…Although the exact structure of this species requires further exploration, our preliminary studies (HMRS and NMR) provide evidence for its formation. 15 Meanwhile, we confirmed that C−Ti and C−Fe bonds coexisted in this species by trapping of C−Ti and C−Fe bonds with different reactions. Using these reactions, we also compared the reactivity of C−Ti and C−Fe bonds in this bimetallic compound.…”
Section: Distinct Reactivity Of C−fe and C−ti Bondsmentioning
confidence: 52%
“…This intriguing dianion synthon can accomplish E/E' type ODFs in a highly regioselective manner relying on the different reactivity of C−Fe and C−Ti bonds. 15 Various electrophilic reactions including alkylation, acylation, amination and phosphorylation occurred smoothly with the promotion of copper(I) salts except the alkylation and amination at Fe site which can react directly with RX or R2NCl. Selected examples and synthetic applications are outlined in Scheme 3.…”
Section: Scheme 3 E/e' Type Difunctionalizations and Synthetic Applic...mentioning
confidence: 99%
See 1 more Smart Citation
“…6 By taking advantage of the Fe/Ti synergism 7,8 to overcome the aforementioned challenges, we have obtained unprecedented 1,2-Fe/Ti heterobimetallic arylene compounds recently. 9 Although these Fe/Ti heterobimetallic compounds have achieved highly regioselective ODFs, stoichiometric FeCl 2 and dppe ligands were required. We herein report a novel Fe-catalyzed protocol for ODF via double C−H activations (Scheme 1C), where the catalyst only requires FeCl 2 /tmeda and the optimal titanate is readily available simple Initially we used the reactions in Scheme 2 as a model to explore the factors affecting the Fe/Ti exchange reaction and the ortho C−H ferration of the C−Ti bond.…”
mentioning
confidence: 99%
“…By taking advantage of the Fe/Ti synergism , to overcome the aforementioned challenges, we have obtained unprecedented 1,2-Fe/Ti heterobimetallic arylene compounds recently . Although these Fe/Ti heterobimetallic compounds have achieved highly regioselective ODFs, stoichiometric FeCl 2 and dppe ligands were required.…”
mentioning
confidence: 99%